Description of Sarcofahrtiopsis spinetta sp. nov. and new records of S. cuneata (Diptera: Sarcophagidae) in South America - Mulieri, Pablo Ricardo (2019)
Fil: Mulieri, Pablo Ricardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina.